Libraries at the heart of dialogue of cultures and religions : history, present, future - Vandermarcq, Fabien; Courau, Thierry-Marie; Vandermarcq, Fabien (Cambridge Scholars Publishing, 2016)
From antiquity until the present, libraries have served to witness cultural and religious exchanges between civilizations. A number of famous libraries have often acted as the cornerstones of the history of humankind in all its diversity. In 2014, in addition to the world congress of the International Federation of Library Associations and Institutions (IFLA), satellite meetings were held in Paris. The theme of these meetings was "Libraries at the Heart of Dialogue of Cultures and Religions". The presentations centred around three aspects: "Religious Libraries and History," "Anticipating and Facing Urgent Issues," and "New Technologies and Networking to Solve Some Issues."The publication of these proceedings allows to draw up a panorama of the questions raised by these themes, highlight some initiatives, and offer solutions or lines of thought to professionals and Library and Information Science students.